Transcending Physical Limits to Enhance the Spiritual Intelligence of Islamic Boarding School Students through Qiyamul Lail - Permana, Irfan Setia (IAIN Palangka Raya, 2024)
The practice of qiyamul lail has become an integral part of Islamic religious culture. Many studies have been conducted on spiritual intelligence and mental health. Still, the specific contribution of qiyamul lail to the development of spiritual intelligence and mental health of students in Islamic boarding schools has not been explicitly researched. The research aimed to analyze efforts to increase the spiritual intelligence of students through qiyamul lail by going beyond physical limitations. The study used a quantitative approach involving participants 10% of the population, namely around 33 participants consisting of Islamic boarding school students and female students. Data was collected through a questionnaire that assessed the frequency of practiced qiyamul lail and measured the level of spiritual intelligence using tested instruments. The F value calculated following data analysis is 11.717 at a significance value of 0.002 < 0.05. Then, Ho is rejected, and Ha is accepted. Apart from that, among students who study at the Muhammadiyah Ki Bagus Hadikusumo Islamic Boarding School, there is quite a high influence between the Qiyamul Lail variable (X) and the Spiritual Intelligence Variable (Y). The coefficient of determination (R square) was 0.274, and the correlation value (R) was 0.524, indicating an influence of 27.4% of the Qiyamul Lail variable on the Spiritual Intelligence variable. The research found that the more often students perform qiyamul lail, the higher their spiritual intelligence development. In addition, linear regression analysis showed the implementation of qiyamul lail contributes 27.4% to the variation in the development of spiritual intelligence of Islamic boarding school students.